Стан репродуктивного здоров'я жінок із доброякісною тиреоїдною патологією - Хабрат, Б. В.; Литвак, О. О.; Лисенко, Б. М.; Хабрат, А. Б.; Гирявенко, О. Я.; Черпак, Б. Д. (Clinical Endocrinology and Endocrine Surgery, 2012)
Women with thyroid disease have high incidence of benign tumors and hyperplastic processes of the reproductive system, which was the greatest in patients with hypothyroidism. These results should be considered in practical public health for diagnostic, therapeutic and prophylactic measures.